Border and Textuality in the Mediterranean: United States and Spain in Transition Towards Democracy under the Cold War (Global Journal of Human-Social Science, 2021)
The Political Transition catalyzed a change process in the Spanish society that would lead to its international standardization The international dimension was the key to understand the nature of the Spanish Policy concerning the Mediterranean Area its close southern periphery and the guidelines of the Modernization in a European and Western sense The reflection about the meaning of the frontier in the historical and cultural background of the United States of America and Spain according to the Mediterranean world is analyzed from these two approaches on the one hand the challenge and the debate about the Modernity and Modernization throughout the 20th century in the special context of the Political Transition and on the other hand the different experiences that were converging from Washington and Madrid around the Mediterranean as a frontier in term of security
Keywords: US foreign policy; spanish foreign policy; democratic transition; european integration; and mediterranean history